Build your dream network : forging powerful relationships in a hyper-connected world - Hoey, J. Kelly (New York : TarcherPerigee, 2017)
'Cut through the networking noise and start building the powerful, real relationships needed to succeed in our digital world,'--Amazon.com.
Build your network -- Get your head in the networking game -- How and where to start -- Clubs, crowds, committees, and cohorts -- #networking -- Connecting the dots -- Networking #fail -- Test, fail, learn, and scale.
Includes bibliographical references.
Keywords: Business networks; Social media; Computers -- Web -- Social